Analisis Wacana Kritis Upaya Pemerintah Mengatasi Pelecehan Seksual Terhadap Perempuan di Transportasi Publik - Firmansyah, Dwi; Adiarsa, Sopyan Resmana; Aryani, Lina (Jurnal Intervensi Sosial dan Pembangunan, 2024)
This research examines PT. Transjakarta's efforts to address sexual harassment in public transportation, specifically within the Transjakarta system, focusing on Norman Fairclough's critical discourse analysis in detik.com news coverage. The research aims to investigate three dimensions of Fairclough—textual analysis, discursive practices, and socio-cultural practices—embedded in the news reporting. The research methodology employed is qualitative with a critical discourse analysis approach to explore and analyze discourse in detik.com news. Data were collected from secondary sources, including relevant news and articles. Data analysis techniques encompass textual analysis to explore representations, relations, and identities in the news, discursive practices to understand text production and consumption, and socio-cultural practices to interpret situational, institutional, and social aspects of the news. The findings indicate that PT. Transjakarta's efforts to combat sexual harassment involve active participation from the Head of the Company Secretary Division, Anang Rizkani Noor, and strategies such as providing women-only buses as a preventive measure. The news also reflects the independence of detik.com journalists in reporting the issue without associated interests.Keywords; Sexual Harassment, Transjakarta, Detik.com.